A regulação financeira sob análise no Brasil e nos EUA - Fernandes, Matheus da Silva (2017)
The purpose of this dissertation is to analyze and propose changes in financial regulation from a Marxist-Keynesian point of view. This study is justified by the lack of social meaning in the functioning of the financial system. From the 1960s, fictitious capital began to take the productive economy more and more. Tax havens serve the wealthiest individuals and large corporations by allowing them to evade rules and taxes they would otherwise be compelled to meet. The financial crisis of 2008 let the dimension of those capitals be clear, which started to withdraw banking and financial regulation and supervision, allowing them to create new financial investments that turned non-bank institutions equivalent to bank institutions. To that end, these shadow banks were financed with customer deposits and invested in securities such as CDOs from subprime mortgages. When mortgage borrowers began to default, the entire system succumbed and carried with them the whole US economy, a priori, and the world economy after. Brazil, however, is involved in another way, by practicing the highest real rates of interest in the world. This fact allows the financial intermediaries to puncture a significant proportion of the productive wealth of families and companies, channeling it to the financial system. High rates of interest also affect the public sector by compromising the government budget with financial expenses instead of expending in public education, healthcare and infrastructure, for example. It is upon governments to restate the order of the financial sector, by enforcing laws that keep the financial system under strict supervision, and extend its scope to newly created innovations. The rates on capital gains and on fortunes should be instituted and raised and the usury crime regulated, establishing a ceiling for real rates of interest in Brazil